Performance Analysis of Multispectral Color Composite Image Enhancement Technique using Decorrelation Stretching and Histogram Equalization Methods - Boopathiraja, S; Kalavathi, P; Geethalakshmi, M (International Journal of Computer Sciences and Engineering, 2025)
Multispectral images are taken from remote sensing sensors which are used in wide variety of application including earth observation, distortion management and so on. An interpretation of those images for different type of applications needs to enhance for more accurate processing. In this study, we have taken the multispectral image of LANDSAT dataset which has seven bands. The color composite image is derived through combining different bands of this dataset and it is act as single color composite multispectral image. The enhancement of this multispectral color composite images is done through decorrelation stretching and the performance of this method is explained and compared with other methods such as various histogram based methods.